Contribution of Involved-field Radiotherapy to Survival in Patients With Relapsed or Refractory Hodgkin Lymphoma Undergoing Autologous Stem Cell Transplantation. (February 2015) - Eroglu, Celalettin; Kaynar, Leylagül; Orhan, Okan; Keklik, Muzaffer; Sahin, Cem; Yildiz, Oğuz G.; Mentes, Selahattin; Kurnaz, Fatih; Aslan, Dicle; Sivgin, Serdar; Soyuer, Serdar; Eser, Bülent; et al.
Abstract : Objectives: To assess the outcomes of overall survival and posttransplantation survival in patients with Hodgkin lymphoma (HL) undergoing autologous stem cell transplantation (ASCT) because of the development of relapse or resistance after chemotherapy (CT) or CT plus radiotherapy (combined modality treatment, CMT). Methods: Forty-five patients undergoing ASCT because of the development of relapse or resistance after CT or CMT for HL were enrolled in the study. Radiotherapy was given as involved-field radiotherapy. Patients were treated with CT alone (n=25) or CMT (n=20). These 2 groups were further divided into 2 subgroups: the patients with early-stage (I to II) and advanced-stage (III to IV) HL. Results: Median patients age was 29 years (range, 16 to 60 y) and the median follow-up was 60 months (range, 12 to 172 mo). In the patients with advanced-stage HL, there was no statistically significant difference in overall survival between irradiated and nonirradiated patients (n=18, irradiated n=4 and nonirradiated n=14). However, in the patients with early-stage disease, there was a significant difference in 5- and 10-year overall survival between the irradiated and nonirradiated groups (81% vs. 48% and 66% vs. 24%, respectively, P =0.045; n=26, irradiated n=16 and nonirradiated n=10). In the univariate analysis, irradiated group and involvement of 1 to 2 nodal regions were found to be significant for overall survival, whereas irradiated group, early stage, and involvement of 1 to 2 nodal regions were found to be significant for posttransplantation survival. However, only irradiated group was found to be significant for posttransplantation survival in multivariate analysis ( P <0.05). Conclusions: Addition of involved-field radiotherapy to CT in patients undergoing ASCT after relapse or recurrence failed to provide survival benefit in patients with advanced HL, while a survival benefit was observed in patients with early-stage HL. Radiotherapy should be considered as part of CMT in the patients with early-stage HL, which should not be neglected.